Forbidden flight - Cohen, Chester (Salt Lake City, UT : Project Gutenberg, 2024)
"Forbidden Flight" by Chester Cohen is a science fiction novel written in the early 20th century. Set against the backdrop of a futuristic society in the 21st century, the book explores the daring and often dangerous aspirations of young space pioneers who dare to journey into the unknown realms of the universe. The central theme revolves around the quest for knowledge and the consequences of ignoring warnings against embarking on perilous expeditions. The story follows a group of ambitious youth known as the Junior Rocketeers as they prepare for an unauthorized expedition to Uranus, despite previous disasters that have befallen their predecessors. Led by the passionate Jason Day and co-pilot Blanche Holm, the crew's enthusiasm is unwavering, though a voice of caution emerges from Dr. Henry Neist, who has been both their supporter and now their reluctant adversary. As the ship named Quest hurtles through space, the crew is filled with excitement and trepidation. However, their journey takes a tragic turn when they encounter the remnants of failed missions, leading to their own devastating fate as their vessel succumbs to the unrelenting forces of the cosmos. The narrative ultimately reflects on the tension between youthful ambition and the harsh realities of exploration. (This is an automatically generated summary.)
Release date is 2024-03-11
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Space flight -- Fiction